Extractives and ash content of oil palm trunk (Elaeis Guineensis) - Mat Din, Muhamad Huzwa; Mohd Sanip, Muhamad Najaaid Izzat; Ahmad Nadzri, Seri Nur Iman Hidayah (2012)
In Malaysia, oil palm (Elaeis guineensis) has become one of the important raw materials with high demand in the wood-based industry. In this study, two chemical components that were studied are extractive and ash content of tree height and distance from the bark to the core. Experiments carried out to determine the chemical composition of this is through solubility of hot water, 1% NaOH and ash content. Both experiments are referring to the TAPPI standards. Meanwhile the results show that the top portion of oil palm trunk has the higher value of extractives and ash content. For the study of effect on layer, layer three (near pith) show there are a lot of extractives and ash content.